Slovakia and North Macedonia: A Comparison of Experiences in Resolving Neighbourly Disputes - Marušiak, Juraj (Identities: Journal for Politics, Gender and Culture, 2023)
The aim of the present article is to compare the experiences of Slovakia and North Macedonia – countries with similar path of problematic nation-state formation and at the same time to identify to what extent Slovakia’s experience in improving relations with its neighbors can serve as an example of “good practice” for North Macedonia. In the case of Slovakia and North Macedonia, which have been chosen as the subject of comparative research, it is possible to speak of the existence of a number of “unresolved” problems in relations with neighboring states, which they have to face as newly “nationalizing” states. In the case of Slovakia, bilateral relations with Hungary are key, in the case of North Macedonia, relations with Greece and Bulgaria. The following research question is, what role the factor of Europeanization of internal and foreign policy played in this case. Paper is comparing the historical genesis of the disputes with the neighboring states as well as their nature and way of solution chosen by both countries. What they have in common is the lack of respect on the part of Bulgaria, or Hungary, for the sovereignty of the neighbouring states. As the issue of the status of minorities abroad is one of the highly sensitive topics of internal politics in both states, and similarly the so-called Hungarian card in Slovakia and the Bulgarian card in North Macedonia, the escalation of the above conflicts depends on the dynamics of internal political developments in the respective countries. For these reasons, there is little chance that a change in the positions of the two states could occur in the short term. Author(s): Juraj Marušiak Title (English): Slovakia and North Macedonia: A Comparison of Experiences in Resolving Neighbourly Disputes Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 40-59 Page Count: 20 Citation (English): Juraj Marušiak, "Slovakia and North Macedonia: A Comparison of Experiences in Resolving Neighbourly Disputes,” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 40-59.